Neuroanatomical Alterations in Patients with Early Stage of Unilateral Pulsatile Tinnitus: A Voxel-Based Morphometry Study - Yawen Liu; Han Lv; Pengfei Zhao; Zhaohui Liu; Wenjing Chen; Shusheng Gong; Zhenchang Wang; Jian-Ming Zhu (Neural Plasticity)
During the past several years, the rapid development of neuroimaging techniques has contributed greatly in the noninvasive imaging studies of tinnitus. The aim of the present study was to explore the brain anatomical alterations in patients with right-sided unilateral pulsatile tinnitus (PT) in the early stage of PT symptom using voxel-based morphometry (VBM) analysis. Twenty-four patients with right-sided pulsatile tinnitus and 24 age- and gender-matched normal controls were recruited to this study. Structural image data preprocessing was performed using VBM8 toolbox. Tinnitus Handicap Inventory (THI) score was acquired in the tinnitus group to assess the severity of tinnitus and tinnitus-related distress. Two-sample t-test and Pearson’s correlation analysis were used in statistical analysis. Patients with unilateral pulsatile tinnitus had significantly increased gray matter (GM) volume in bilateral superior temporal gyrus compared with the normal controls. However, the left cerebellum posterior lobe, left frontal superior orbital lobe (gyrus rectus), right middle occipital gyrus (MOG), and bilateral putamen showed significantly decreased brain volumes. This was the first study which demonstrated the features of neuroanatomical changes in patients with unilateral PT during their early stages of the symptom.